2014
DOI: 10.1088/0256-307x/31/12/127401
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Single-Crystal Neutron Scattering Study of Magnetic and Fe Vacancy Orders in (Tl,Rb) 2 Fe 4 Se 5 Superconductor

Abstract: The magnetic and iron vacancy orders in superconducting (Tl,Rb)2Fe4Se5 single-crystals were investigated using a high-pressure neutron diffraction technique. Similar to the temperature effect, the block antiferromagnetic order gradually decreases upon increasing pressure while the Fe vacancy superstructural order remains intact before its precipitous disappearance at the critical pressure Pc =8.3 GPa. Combined with previously determined Pc for superconductivity, our phase diagram under pressure reveals the con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
(69 reference statements)
2
14
0
Order By: Relevance
“…Upon increasing pressure, the hump is suppressed significantly, same as that seen in the pressurized K-245 and Tl(Rb)-245 superconductors [30,32]. At pressure ∼8.4 GPa, we found that the resistance hump becomes almost featureless, which is signed the destruction of the long-ranged AFM order [34]. Zooming in the plot of R-T curve in the low temperature range, the pressureinduced decrease in Tc is shown more clearly ( figure 1(b)).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Upon increasing pressure, the hump is suppressed significantly, same as that seen in the pressurized K-245 and Tl(Rb)-245 superconductors [30,32]. At pressure ∼8.4 GPa, we found that the resistance hump becomes almost featureless, which is signed the destruction of the long-ranged AFM order [34]. Zooming in the plot of R-T curve in the low temperature range, the pressureinduced decrease in Tc is shown more clearly ( figure 1(b)).…”
Section: Resultssupporting
confidence: 71%
“…Our results reveal that the Tc of the SC-I phase in the A-245 superconductors is very sensitive to the local lattice distortion from Te doping. It is noteworthy that neither the SC-I nor SC-II phases is observed in the sample of x = 0.4, at the doping level of which the long-ranged AFM order at ambient pressure is fully suppressed [30,34,36,37] (upper right panel of figure 4). No observable sign exists of the SC-II phase, even when the paramagnetic semiconducting sample (x = 0.4) is pressurized into a metallic state (figures 3(d) and (e) and 4).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Comparing with the evolution of AFM order with pressure in Fe-based pnictides4344 and chalcogenides4546 whose AFM order can be destroyed at modest pressure below ~10 GPa, the AFM order in the K-doped BaMn 2 Bi 2 exhibits insensitive to pressure. These results demonstrates that the Mn's d 5 electrons in the sample investigated are much more localized than Fe's d 6 electrons in the Fe-based pnictides and Fe-based chalcogenides, which leads to the K-doped BaMn 2 Bi 2 belongs to a strong Hund's AFM metal with a hybridization between localized spin electrons and itinerant electrons.…”
Section: Discussionmentioning
confidence: 99%